Ultrastructure of cell trafficking pathways and coronavirus: how to recognise the wolf amongst the sheep. Issue 4 (22nd October 2020) - Neil, Desley; Moran, Linda; Horsfield, Catherine; Curtis, Elizabeth; Swann, Olivia; Barclay, Wendy; Hanley, Brian; Hollinshead, Michael; Roufosse, Candice
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic has resulted in an urgent need to understand the pathophysiology of SARS‐CoV‐2 infection, to assist in the identification of treatment strategies. Viral tissue tropism is an active area of investigation, one approach to which is identification of virus within tissues by electron microscopy of post‐mortem and surgical specimens. Most diagnostic histopathologists have limited understanding of the ultrastructural features of normal cell trafficking pathways, which can resemble intra‐ and extracellular coronavirus; in addition, viral replication pathways make use of these trafficking pathways. Herein, we review these pathways and their ultrastructural appearances, with emphasis on structures which may be confused with coronavirus. In particular, we draw attention to the fact that, when using routine fixation and processing, the typical 'crown' that characterises a coronavirus is not readily identified on intracellular virions, which are located in membrane‐bound vacuoles. In addition, the viral nucleocapsid is seen as black dots within the virion and is more discriminatory in differentiating virions from other cellular structures. The identification of the viral replication organelle, a collection of membranous structures (convoluted membranes) seen at a relatively low scanning power, may help to draw attention to infected cells, which can be sparse. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.